Antimalarial activity of Syzygium guineense during early and established Plasmodium infection in rodent models. Issue 1 (December 2017) - Tadesse, Solomon; Wubneh, Zewdu
Abstract Background In Ethiopia, the leaves ofSyzygium guineense have been found useful for the prevention and cure of malaria, and demonstrated antiplasmodial activity in vitro. Nevertheless, no scientific study has been conducted to confirm its antimalarial activity in vivo. Therefore, the objective of the study was to evaluate the antimalarial effect ofSyzygium guineense leaf extract in mice. Methods Inoculation of the study mice was carried out by using the malaria parasite, Plasmodium berghei . The plant extract was prepared at 200, 400 and 600 mg/kg. Chloroquine and distilled water was administered to the positive and negative control groups respectively. Parameters like parasitaemia, survival time and body weight were determined following standard tests (4-day suppressive, Rane's and repository tests). Results Syzygium guineense crude leaf extract displayed considerable (p < 0.05) parasite suppression at doses of 600 and 400 mg/kg in a 4-day suppressive test with chemosuppressive value of 59.39 and 49.09% respectively.S. guineense crude leaf extract also showed dose-dependent schizontocidal activity in both the repository and curative tests. The extract also prevented body weight loss and prolonged survival date of mice significantly (P < 0.05) at the highest dose employed in the study. Qualitative chemical assay forS. guineense methanolic leaf extract revealed that the plant is endowed with different plant secondary metabolites exemplified by terpenoids, alkaloids, triterpenes, flavonoids, anthraquinones, tannins, glycosides, saponins and phenols. Conclusion Syzygium guineense leaf extract possess antimalarial activity in mice. The test substance was found to be safe with no observable signs of toxicity in the study mice. The results of the present work confirmed the in vitro antiplasmodial finding and traditional claims in vivo in mice. Therefore, Syzygium guineense could be regarded as a potential source to develop safe, effective and affordable antimalarial agent.